Cortisol awakening response and heart rate variability in the menstrual cycle of sportswomen - Kayacan, Y.; Makaraci, Y.; Ozgocer, T.; Ucar, C.; Yildiz, S. (Research Quarterly for Exercise and Sport, 2021)
Purpose: This study aimed to examine the activities of heart rate variability (HRV) and cortisol secretion as markers of the autonomous nervous system (ANS) and the hypothalamic-pituitary-adrenal axis (HPA) during the menstrual cycle in female athletes.